Using principal component analysis to investigate pacing strategies in elite international canoe kayak sprint races - Goreham, J. A.; Landry, S. C.; Kozey, J. W.; Smith, B.; Ladouceur, M. (Sports Biomechanics, 2023)
The aim of this research was to use principal component analysis (PCA) to investigate the current pacing strategies of elite canoe kayak sprint athletes and to determine if there are differences in pacing patterns between medallists and non-medallists at major international competitions. Velocity data collected using global positioning systems (GPS) from all a-finals of major international competitions in 2016-2017 (including canoe and kayak, single and crew boat, and male and female) were downloaded from the International Canoe Federation's website. Data were normalised by the average velocity within each race and organised by race distance. In total 10, 14 and 16 races were analysed, and they followed all-out, positive, and "seahorse-shaped" pacing strategies for the 200 m, 500 m, and 1000 m events, respectively. Normalised velocity PC1 (p =0.039, ES=-0.44) and PC2 scores (p <0.001, ES=-0.73) for 1000 m races were significantly different between medallists and non-medallists; however, significant differences between PCs were not found between groups in shorter race distances (i.e. 200 m and 500 m). Data collected using GPS provide information that can be used to better prepare athletes for canoe kayak sprint races lasting between 30 s and 240 s in duration.